2007
DOI: 10.1063/1.2780191
|View full text |Cite
|
Sign up to set email alerts
|

Single magnetic particle dynamics in a microchannel

Abstract: Functionalized magnetic particles are used in micrototal analysis systems since they act as magnetically steered mobile substrates in microfluidic channels, and can be collected for bioanalytical processing. Here, we examine the motion of magnetic microbeads in a microfluidic flow under the influence of a nonuniform external magnetic field and characterize their collection in terms of the magnetic field strength, particle size, magnetic susceptibility, host fluid velocity and viscosity, and the characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 23 publications
1
55
0
Order By: Relevance
“…This result implies that while the fluid exerts drag on each particle, the particles exert no force on the fluid. 41,42 Furthermore, the number of particles within the suspension is assumed dilute, thus there exists no short-range interparticle dipolar interaction. As the magnetic particle is carried by the flowing solution in the y -direction, within the context of laminar flow, the hydrodynamic forces only act in the x -direction ͑direction perpendicular to flow͒.…”
Section: B Hydrodynamic Resistance Force Determinationmentioning
confidence: 99%
“…This result implies that while the fluid exerts drag on each particle, the particles exert no force on the fluid. 41,42 Furthermore, the number of particles within the suspension is assumed dilute, thus there exists no short-range interparticle dipolar interaction. As the magnetic particle is carried by the flowing solution in the y -direction, within the context of laminar flow, the hydrodynamic forces only act in the x -direction ͑direction perpendicular to flow͒.…”
Section: B Hydrodynamic Resistance Force Determinationmentioning
confidence: 99%
“…For example, the chain formation process of magnetic particles in an external magnetic field and under Molecular Dynamics -Theoretical Developments and Applications in Nanotechnology and Energy 216 the effects of shear in microchannels was analyzed and the chain growth rate predicted by the Smoluchowski model was observed to be consistent with experimental observations (Brunet et al, 2005). The transport of an isolated magnetic microsphere or of very dilute suspensions where dipole-dipole interactions are negligible through a microchannel have also been investigated both experimentally and numerically (Sinha et al, 2007). The controlled aggregation of Janus magnetic nanoparticles was studied using dynamic light scattering and cryo-TEM imaging techniques and the main features of the aggregation behavior were consistent with predictions provided by a modified version of the classic Monte Carlo simulation algorithm (Lattuada and Hatton, 2007).…”
Section: Introductionmentioning
confidence: 49%
“…Sinha et al, 9 through dimensional reasoning, identify a parameter that characterizes the critical magnetic bead entrance position at which eventual bead capture 20 takes place before the channel exit. Their parameter is equivalent to Ω, albeit modified by the inverse aspect ratio y c /l m , which reinforces our more detailed scaling-law argument.…”
Section: Scaling Analysismentioning
confidence: 99%
“…Theoretical models of bead trajectories and capture efficiencies have also been developed. [9][10][11][12][13][14][15][16][17] To date, these models and experiments 25 demonstrate that microfluidic immunomagnetic systems can collect a single target from a solution of many targets. Pamme et al [18][19] experimentally demonstrated that microfluidic magnetic systems can potentially sort multiple targets.…”
Section: Introductionmentioning
confidence: 99%